TECHNICAL AND COST ANALYSIS OF FLOOD CONTROL PLANNING USING THE ECODRAINS-BASED SPONGE VILLAGE MODEL IN THE KAMONING SAMPANG WATERSHED - Muqaddas, Zaiful; Tjendani, Hanie Teki; Witjaksana, Budi (Transpublika Publisher, 2024)
The Kali Kamoning Watershed in Sampang Regency, spanning 35,421.15 Ha, experiences annual major floods affecting Sampang City. Despite various attempts and budget allocations at different administrative levels, flooding remains a persistent issue. A proposed solution is the implementation of an Ecodrains-based sponge village model for flood control, specifically targeting upstream areas like Karang Penang, Robatal, Kedungdung, Omben, and Sampang sub-districts. The model, cost-effective and easy to construct, utilizes the HEC-HMS software for technical analysis, simulating river capacity and calculating flood reduction. The sponge village model demonstrates a substantial reduction of flooding by 73.14%, equivalent to 326.3 m3/sec. The Q25th flood discharge measures 446.1 m3/sec. Estimated construction costs using the SNI method amount to IDR 917,588,260,000, aiming to control the Q25th flood. This innovative approach offers a promising strategy for mitigating flooding in Sampang City through sustainable watershed management and cost-efficient infrastructure development. Key terms: Watershed, Flood Reduction, Ecodrains, Sponge Village Model, HEC-HMS, Q25th, Construction Costs.